2021
DOI: 10.1007/s40299-021-00572-y
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Online Home-Based Learning and Students’ Engagement During the COVID-19 Pandemic: A Case Study of Singapore Mathematics Teachers

Abstract: The COVID-19 pandemic has forced school closure thus shifting teaching and learning towards full home-based learning (HBL). Technology plays a key role but the considerations to design online learning environments that meaningfully engage students are complex. This exploratory, qualitative study attempted to elicit eight mathematics teachers’ considerations and perspectives in designing online home-based learning lessons for the engagement of elementary and secondary students. Data were gathered through interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 26 publications
2
62
0
7
Order By: Relevance
“…Siswa dengan keterampilan teknologi yang lemah, dan tidak memiliki dukungan perangkat dan jaringan internet yang memadai (Baloran, 2020) akan merasa kesulitan dalam mengikuti kegiatan pembelajaran. Selain itu, perasaan tidak adil akan muncul pada diri siswa, yang mengakibatkan siswa tidak memperoleh pembelajaran dengan maksimal (Hebebci et al, 2020;Tay et al, 2021). Hal ini didukung oleh temuan Sehoole (2020) dimana pembelajaran jarak jauh berbasis teknologi telah menantang sistem pendidikan di seluruh dunia untuk memanfaatkan pandemi Covid-19 dalam menjembatani kesenjangan antara si kaya dan si miskin dalam hal akses pendidikan, dan tantangan ini masih belum terpecahkan hingga saat ini.…”
Section: Tahap 3: Penilaian Kritis Pada Data Literature (Critical Appraisal Of Sample)unclassified
“…Siswa dengan keterampilan teknologi yang lemah, dan tidak memiliki dukungan perangkat dan jaringan internet yang memadai (Baloran, 2020) akan merasa kesulitan dalam mengikuti kegiatan pembelajaran. Selain itu, perasaan tidak adil akan muncul pada diri siswa, yang mengakibatkan siswa tidak memperoleh pembelajaran dengan maksimal (Hebebci et al, 2020;Tay et al, 2021). Hal ini didukung oleh temuan Sehoole (2020) dimana pembelajaran jarak jauh berbasis teknologi telah menantang sistem pendidikan di seluruh dunia untuk memanfaatkan pandemi Covid-19 dalam menjembatani kesenjangan antara si kaya dan si miskin dalam hal akses pendidikan, dan tantangan ini masih belum terpecahkan hingga saat ini.…”
Section: Tahap 3: Penilaian Kritis Pada Data Literature (Critical Appraisal Of Sample)unclassified
“…With higher education (HE) academic programmes offered entirely online as a result of the COVID-19 pandemic of 2020, large-scale change has been required of academic staff who design and present the programmes and of their students who undertake them. On-campus face-to-face teaching will most likely return when the pandemic abates, providing the social-cultural elements of the teacher, the learning environment, technology, learning activities and peers that in undergraduate education support effective student engagement (Crosling et al, 2008;Tay et al, 2021) and students' development of higher-level skills such as problem-solving and technical skills (Saavedra & Opfer, 2012;Dhawan, 2020;Chandra, 2020). It is interesting to note that during the pandemic, students' preferences for online compared with face-to-face shifted worldwide: 78% of tertiary students in Malaysia, 83% in Canada and 78% in China indicated a preference for online learning, if programme fees are reduced accordingly (Karupiah, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of academic staff's BL experiences, challenges, solutions and suggestions for improvement is valuable for enhanced implementation. In Singapore, while education has benefited from Information and Communication Technology (ICT) for more than two decades (Tay et al, 2021), the post-pandemic period of HE BL implementation presents different challenges and opportunities in new pedagogical forms. However, effective BL should be underpinned by an ecosystem (Dhawan, 2020) that reflects the changing relationship between stakeholders (Nikolaidou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Universities and schools have been caught unprepared for this case (Lin, 2021 ). Although people are not ready for online training, the transition process to online training has been started in order not to interrupt the training (Azhari & Fajri, 2021 ; Erkut, 2020 ; Lin, 2021 ; Ozalkan, 2021 ; Tay et al, 2021 ). It has been observed that students and adults can carry out some of their work from home.…”
Section: Introductionmentioning
confidence: 99%